An Iterative Algorithm for Solving Generalized Variational Inequalities and Fixed Points Problems - Yonghong Yao; Mihai Postolache; Jen-Chih Yao (Mathematics, 2019)
In this paper, a generalized variational inequality and fixed points problem is presented. An iterative algorithm is introduced for finding a solution of the generalized variational inequalities and fixed point of two quasi-pseudocontractive operators under a nonlinear transformation. Strong convergence of the suggested algorithm is demonstrated.